Wartościowanie w tabloidzie jako zamierzony środek oddziaływania na odbiorcę - Czajka-Bubniak, Anna (Słowo. Studia językoznawcze, 2017)
The main aim of the study is showing how tabloid try to evaluate the reality. Tabloid “Fact” is a paper which negates all the social injustices associated with luxury, richness and a defiance of simple people. Tabloid is often the only one paper which people want to read, so it is directed at easy entertainment and sensation. Editors use various rhetorical means, (stylistic and lexical), popular slogans to manipulate the society. The tabloid evaluates positive and negative through the headlines and pictures. The resume of the study is a reconstruction of values which are postulated by “Fact” and based on flagships words recommended by Walery Pisarek.